Sustainability Analysis of Craft Business in Mekar Sari Village, Asahan Regency: An Islamic Economic Review - Harahap, Astri Sri Rezeki; Yusrizal, Yusrizal; Syahbudi, Muhammad (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: This study aims to determine the sustainability of the craft business in Mekar Sari Village, Asahan Regency. Design/Method/Approach: This study uses a qualitative descriptive method. The data collection techniques include interviews, observations, questionnaires, and documentation. The subjects in the primary data collection consisted of five informants: palm broom business owners, business workers, business treasurers, and two product buyers. Secondary data were obtained from various relevant literature sources, such as books, scientific journals, online articles, and documents that support this research. This study adopts the SWOT analysis method to identify and eliminate various factors affecting microenterprises’ development. This analysis will divide internal factors affecting micro businesses into two main categories: strengths and weaknesses. On the other hand, the analysis will also include external factors that involve opportunities that can be used for the advancement of micro businesses, as well as threats that can be challenges or risks that need to be watched out for. Findings: The results of this study show that micro businesses with palm oil brooms obtained an IFAS score of 3.428571 and an EFAS score of 3.363636, which puts them in quadrant III. In the quadrant, the suggested strategy is a turnaround strategy, which aims to reduce internal weaknesses by taking advantage of existing opportunities. This turnaround strategy can be integrated with Islamic economics, focusing on justice, social responsibility, sustainability, and community empowerment. Originality/Values: This study’s implications can Help develop the palm oil broom craft business by using a SWOT analysis development strategy that includes strengths, weaknesses, opportunities, and threats, combining the Triple Bottom Line (TBL) concept. Thus, this craft business can develop not only in terms of profit but also make a positive contribution to the community and the surrounding environment, which ultimately increases market attractiveness and supports the sustainability of the craft business in palm oil brooms in the long term.